PENGARUH INFLUENCE STRATEGIES KELUARGA TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG GALAXY A SERIES DI BANDAR LAMPUNG - Ramadona, Dewi Monica Prihartini; Hatono, Hartono; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
This research aims to find out the effect of family influence strategies on Samsung Galaxy A Series mobile phone costumer purchasing decisions in Bandar Lampung. The independent variable that used in this research are Family Influence Strategies (X) and Purchasing Decisions as dependent variable. The data in this research are primary data taken using a questionnaire distributed directly at the Urip Cellular mobile phone counter and distributed via google form that shared via social media. The samples in this research amounted to 100 samples that taken by using purposive sampling techniques. The data in this research was analyzed by using simple linear regression with simultaneous variable results of Family Influence Strategies has a significant effect on custome’s purchasing decisions for Samsung Galaxy A Series mobile phones in Bandar Lampung with a value of R Square is 0.453 or 45.3%.